Digital transformation in the distribution and exhibition channels of auteur cinema - Curi, Jimmy Trevejo (2022)
Peruvian auteur cinema has faced problems of distribution and cinematographic exhibition in the windows of massive scope. Most of the exhibition windows have been monopolized by big Hollywood productions. Currently, the mandatory confinement due to COVID-19 has accelerated and materialized a digital transformation process that was under development. That is why the main objective of the research seeks to analyze how the digital transformation in the distribution and exhibition channels contributes to Peruvian auteur cinema. In order to carry out this objective, an interpretative research was conducted with a qualitative data methodology. The selected categories were: auteur cinema, digital transformation and distribution and exhibition channels. Semi-structured interviews were conducted with specialists in marketing and film production. In conclusion, from the perspective of the specialists, it is indicated that such transformation allows opening markets and serving audiences that were historically neglected before. Finally, there was a lack of specialization in the different areas of distribution and audience development, demonstrating the importance of the participation of professionals specialized in marketing to lead these processes. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.